Is the PCA3 cost-effective in Latin America and the Caribbean? - José Antonio Grández-Urbina; Rafael Pichardo-Rodríguez; Jorge Saldaña-Gallo (Instituto Nacional de Salud Pública, 2017)
[Not available]